1991
DOI: 10.1093/ije/20.3.749
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Pollution and Respiratory Illness in a Himalayan Village

Abstract: Summer and winter surveys of a village in Ladakh have been used to study respiratory illness and domestic pollution from fires in an arid high altitude region of northern India. The prevalence of chronic cough with chronic phlegm rose steeply with age, and was greater among women than men. The percentage of villagers with a forced expiratory volume in one second/forced vital capacity (FEV1/FVC) ratio of less than 65% also rose with age, to include 24% of men and 32% of women over 50 years in the summer survey.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1
4

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 0 publications
2
52
1
4
Order By: Relevance
“…Given the high ambient (room) levels, these findings for COHb are consistent with an ethnographic study in this part of western Guatemala that found that women spend between 4.6-6.8 hr per day in the house while the fire is lit (32). The current World Health Organization air quality guidelines recommend exposure to CO of no more than 10 ppm for an 8-hr period and 30 ppm for 1 hr (18), levels that are frequently reached or exceeded in homes burning biomass on open fires.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Given the high ambient (room) levels, these findings for COHb are consistent with an ethnographic study in this part of western Guatemala that found that women spend between 4.6-6.8 hr per day in the house while the fire is lit (32). The current World Health Organization air quality guidelines recommend exposure to CO of no more than 10 ppm for an 8-hr period and 30 ppm for 1 hr (18), levels that are frequently reached or exceeded in homes burning biomass on open fires.…”
Section: Discussionsupporting
confidence: 87%
“…Another key issue is whether wood fuel users really did have higher exposure to pollutants, particularly to CO, and whether the level of exposure they experienced was sufficient to impair fetal growth. Although exposure was not measured directly in the current study, there is fairly substantial evidence from Guatemala (16,(29)(30)(31)(32) and elsewhere (15,17,24,33,34) to answer these questions. Studies from many parts of the world have shown that women are exposed to very high levels of indoor air pollution from biofuels: Typical 24-hr values for particulate matter (PM) 10 are around 1,000 µg/m 3 or higher (15,21,24,33).…”
Section: Discussionmentioning
confidence: 85%
“…First, improved lung mechanics may be an important adaptation to indoor biomass and outdoor dust exposure in high-altitude populations [1]. Norboo et al [2] reported that the prevalence of chronic cough was greater among women than among men. The percentage of villagers over 50 years of age with a forced expiratory volume in 1 s/forced vital capacity ratio (FEV 1.0 /FVC) of less than 65% was 24% in men and 32% in women.…”
Section: Discussionmentioning
confidence: 99%
“…Sixth, it has been reported that in Ladakh, silicosis is widespread among older people exposed to environmental dust. This may result in advanced fibrotic lung disease associated with disability [7][8][9][10]. Saiyed et al [9] reported that environmental dust was associated with the severity of dust storms and the use of chimneys in the kitchens.…”
Section: Discussionmentioning
confidence: 99%